2019
DOI: 10.26803/ijlter.18.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese High School Students’ Perceptions of Academic Advising

Abstract: The purpose of this study is to examine the relationship between the current existing obstacle and Vietnamese high school students' need for academic advising. A group of 1,200 children (449 boys and 751 girls from grade 6 through 12) from seven high schools participated in the survey. They completed a 24-item questionnaire about their study obstacle and academic advising need. The results showed a significant positive correlation between high school students' current existing obstacles and their need for acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In the study by Nguyen, Go [43], the majority of participants rated mental health services as highly essential, and counseling was ordered as more critical than medication. To our best knowledge, the previous research in Vietnam showed that high school students have the need for advising and counseling, but only in the academic aspect [44]. This will be the rst study in the Vietnamese context to investigate the relationship between students' di culties, consultation requirements, requests for psychological services, and factors in uencing the use of psychological services.…”
Section: The Difference Between Grade-level In Student's DI Culty Cou...mentioning
confidence: 90%
“…In the study by Nguyen, Go [43], the majority of participants rated mental health services as highly essential, and counseling was ordered as more critical than medication. To our best knowledge, the previous research in Vietnam showed that high school students have the need for advising and counseling, but only in the academic aspect [44]. This will be the rst study in the Vietnamese context to investigate the relationship between students' di culties, consultation requirements, requests for psychological services, and factors in uencing the use of psychological services.…”
Section: The Difference Between Grade-level In Student's DI Culty Cou...mentioning
confidence: 90%
“…Career counseling is one of the responsibilities of teachers and school counselors in Vietnam's high schools (Van Huynh & Tran-Chi, 2019). There are examples of effective career counseling programs in Vietnamese high schools despite these challenges.…”
Section: Effectiveness Of Career Counseling In Vietnamese High Schoolsmentioning
confidence: 99%
“…Additionally, the ability to develop educational topics tailored to students' needs signifies a teacher's proficiency in addressing the unique learning requirements of their students (Anderson & Stillman, 2013;Muñoz et al, 2022;Uerz et al, 2018). According to Huynh and Tran-Chi (2019), students who encounter challenges in their academic pursuits should seek advise and knowledge regarding these issues. This proficiency allows teachers to create a more engaging and effective learning environment, as they can adapt their teaching methods and materials to suit the individual strengths and weaknesses of each student.…”
Section: Introductionmentioning
confidence: 99%